Investigation of gender representation in illustrations in Iraqi high school textbooks (مجلة ديالى للبحوث الانسانية, 2023)
Textbook takes a vital  role whereas  gender is  socialized in schools . The roles and responsibilities that men and women have in society should be presented to students in textbooks in a balanced way. The major goal of the current study is to examine gender representation in English textbooks that are  taught in public high schools in Iraq and how illustrations are employed in the three English textbooks of fourth , fifth , and six preparatory grades.                   This study employs both quantitative and qualitative analyses. Thus, the data  is collected  by focusing on counting the number of   occurrences of both genders in textbook ,and provide a qualitative examination of illustrations . The framework of Fairclough's (1989) Critical Discourse Analysis  is utilized to analyze the data. that includes three dimensions; description, interpretation, and explanation. The analyses of  this study includes visibility in illustrations. The findings of both qualitative and quantitative analyses show that educational materials are both gender biased and  conventionally stereotyped, despite the efforts of government to achieve equity  in EFL textbooks. It has proved from the results of the  three selected textbooks that males have outnumbered females. Furthermore, the current research provides some pedagogical implications and suggestions that can aid to address the issue of gender unfairness in EFL educational materials .